Can you imagine this? Imagined contact as a strategy to promote positive intergroup relations - Shamoa-Nir, Lipaz; Razpurker-Apfeld, Irene (Frontiers in Psychology, 2023)
In comparison to the extensive body of research on intergroup contact, which encompasses predictors, outcomes, and implications, there has been relatively little attention given to the role of imagined contact with diverse ethno-religious out-groups. This gap particularly exists in understanding the factors that contribute to the effectiveness of imagined contact interventions. This article aims to address this gap by presenting current research on the predictors and consequences of imagined contact. We offer an overview of the circumstances in which imagined contact proves beneficial; while focusing on research that holds relevance for designing interventions and policies promoting contact between culturally and religiously diverse groups and individuals. We also acknowledge the existing limitations within this field of study and propose potential direction for future research.